Prognostic significance of some clinical psycho-physiological signs in women - IDPs with Threatened Interruption of Pregnancy, Living in Lugansk Region - I. Yu. Romanenko (Kazimierz Wielki University, 2020)
The threatened interruption of pregnancy (TIP) is the most common pregnancy complication that occurs in 15-20% of cases of ongoing pregnancy. Chronic stress can affect the course of pregnancy, leading to an increase in the number of complications. The aim of the study was to develop a mathematical model for assessing the risk of premature birth in IDPs women with threatened interruption of pregnancy in the I and II trimesters, living in the Lugansk region in the area of armed conflict in Eastern Ukraine, to improve treatment and prophylactic measures and prevent obstetric and perinatal complications in such women. Material and methods. The study included 220 pregnant women in first and second trimesters of pregnancy who were hospitalized regarding threatened miscarriage in the hospitals, located in the Luhansk region, 47 women of which had IDPs status. The control group consisted of 30 pregnant women with non-complicated obstetric anamnesis and physiological course of pregnancy with similar gestational period of pregnancy and place of residence. The General clinical laboratory test, biochemical blood tests, coagulogram, colpocytology, pH determination and microscopic examination of the vaginal content, concentrations of estradiol, progesterone, prolactin, cortisol, dehydroepiandrosterone sulfate, testosterone, thyroid stimulating hormone (TSH), serotonin, vitamin 25-(OH)D were carried out. Psychological research included the Beck's depression Inventory, Spielberger State-Trait Anxiety Inventory, The Pittsburgh Sleep Quality Index (PICS). The subjective severity of headache (tension-type headache (TTH) and migraine) was determined by visual analogue scale (VAS). Results and discussion. The following discriminant variables can be predictors of the risk of premature birth: a displacement factor, a presence of comorbidities, diseases of the urinary tract, bacterial vaginosis, indicators of Beck's depression Inventory, State and Trait anxiety, autonomic dystonia, PICS, concentrations of TSH, progesterone, DHEA-s, cortisol, serotonin, vitamin 25-(OH)D, an expressiveness of TTH by VAS. Conclusions. The developed mathematical model for assessing the risk of preterm birth in IDPs women has an informative value of 88.2% and can be used for primary screening. The above formula allows us to identify a group of patients who need further in-depth diagnostic search and indications for preventive measures.